2018
DOI: 10.1007/s00592-018-1230-z
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 is a biomarker for cardiovascular mortality related to abnormal glucose metabolism in high-risk subjects

Abstract: Aims Inflammation plays a role in the development and progression of type 2 diabetes macroangiopathy. Interleukin 33 (IL-33) drives production of Th2-associated cytokines. The soluble form of suppression of tumorigenicity 2 (sST2) acting as a decoy receptor blocks IL-33 and tones down Th2 inflammatory response. We investigated the role of sST2 as a predictor of CV and all-cause mortality in a cohort of patients affected by established atherosclerotic disease. Methods 399 patients with atherosclerotic disease f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Univariate ANOVA was used to compare each of the reported variables in the a-NSW, f-NSW and control groups as described [ 16 ]. The Mann–Whitney test was used for variables with non-normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Univariate ANOVA was used to compare each of the reported variables in the a-NSW, f-NSW and control groups as described [ 16 ]. The Mann–Whitney test was used for variables with non-normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…13 Importantly, studies have shown that sST2 is elevated in individuals with T2D, [14][15][16] post-transplant diabetes mellitus, 17,18 and CVD. 19,20 Moreover, sST2 is associated with markers of metabolic dysfunction in atherosclerotic disease, 21 and with increased CVD mortality. 21,22 It has also been shown to be elevated in other inflammatory conditions such as inflammatory bowel disease, 23 gut mucosal damage, 3 and sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identification of early biomarkers that may be associated with the onset of cardiometabolic disease is of considerable importance. Since elevated levels of sST2 are associated with both CVD [19][20][21][22] and T2D, [14][15][16] we hypothesized that sST2 may serve as a novel biomarker to detect subclinical CVD risk in the earliest stages of metabolic disease development. Therefore, we conducted a preliminary study to determine whether sST2 is correlated with glycated haemoglobin (HbA1c) in individuals with glycemia in the normal/prediabetes range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that Metabolic Syndrome (MetS), defined as a cluster of interconnected metabolic risk factors (including abdominal obesity, elevated fasting glucose, hypertriglyceridemia, hypertension, and low High-Density Lipoprotein (HDL) cholesterol levels), increases the risk for atherosclerosis and cardiovascular disease [1][2][3][4][5][6]. In addition, the recent interest of the scientific community has focused on the possible involvement of insulin resistance as a linking factor [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%